2016
DOI: 10.3390/ijerph13070741
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and Risk Assessment of Heavy Metals in Lake Bed Sediment of a Large Lake Scenic Area in China

Abstract: The exposure of heavy metals to lake bed sediment of scenic areas may pose risks on aquatic ecosystems and human health, however very few studies on risk assessment have been reported for scenic areas. Accordingly, this study determined concentration levels, and assessed contamination characteristics and risks, of heavy metals in lake bed sediment of National Scenic Areas Songhuahu (NSAS) in China. The concentrations of Zn, Cr, Pb, Ni, and Cu were determined in 29 bed sediment samples. Results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Heavily polluted sediments in rivers have gradually become a significant factor in water pollution, especially in developing countries [ 1 ]. Since the water in urban rivers is relatively static, the concentrations of pollutants in the sediment, such as organic matter, ammonium nitrogen, phosphorus, and heavy metals are significantly higher than in the overlying water [ 2 , 3 , 4 , 5 , 6 , 7 ]. Sediment and overlying water are continuously exchanging material and energy, so that the pollutants maintain a dynamic equilibrium of adsorption and release [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heavily polluted sediments in rivers have gradually become a significant factor in water pollution, especially in developing countries [ 1 ]. Since the water in urban rivers is relatively static, the concentrations of pollutants in the sediment, such as organic matter, ammonium nitrogen, phosphorus, and heavy metals are significantly higher than in the overlying water [ 2 , 3 , 4 , 5 , 6 , 7 ]. Sediment and overlying water are continuously exchanging material and energy, so that the pollutants maintain a dynamic equilibrium of adsorption and release [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cevik et al [3] reported that SQGs are useful for the assessment of the health of sediment ecosystems as well as the protection of benthic organisms in freshwater ecosystems. Apart from various SQGs, some other indices have been formulated to test the contamination level and ecological risk of single and total heavy metals in sediments for example the geoaccumulation index (I geo ), enrichment factor (EF), Newrow integrated pollution index (P n ), contamination factor (CF) and ecological risk index (RI) [4][5][6][7][8][9]. Background levels of heavy metals in sediments of various countries are often required to calculate the relative toxicity of heavy metals in sediments but due to lack of such data in some countries, average heavy metals levels in sedimentary rock, continental crust, world shale, among others are often employed [1,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…2 = 400 (7 + 8.5) 2 = 1.665 (16) As one may observe, this value of 1.665 from Equation (16) is identical to the pollution index value given by Popa's method (1.665). This may be explained by the fact that Equation (15) is a mathematical reordering of the initial Equation (4) that can be obtained after explicit substitution of the average value via its components in Equation (4).…”
Section: Estimation Of the Index Of Global Pollution For A Thermoelecmentioning
confidence: 55%
“…In case of the environmental component Water, the common quality indicators are: COD, BOD, suspended solids, floating solids, oily products, dissolved substances such as salts or phenols, and others. Likewise, water pollution index might be estimated using a single value by decreasing the number of parameters and representing data in a simple way [14][15][16][17]. According to some previous research papers [18][19][20][21][22], the representative quality indicators for Soil are: total organic carbon (TOC), extractible compounds, soil pH, etc.…”
mentioning
confidence: 99%